Indigenization of Pakistani English in Kanza Javed’s Ashes, Wine and Dust - Maryam Arshad; Humaira Irfan Irfan; Rashid Hussain; Nurah Saleh Alfares (Studies in English Language and Education)
This article explores the indigenization of English in Pakistan in Kanza Javed’s English novel ‘Ashes, Wine and Dust’. This exploratory and interpretative research employed a close reading of the novel to analyse lexical borrowing in Pakistani English, utilising a note-taking technique to identify incorporated Urdu words, examining linguistic features such as semantic fields. The analysis following established frameworks that focus on lexical borrowing and variation as reflections of socio-linguistic practices. The research aimed to explore two key questions regarding lexical variation in this novel. First, the study examined how Javed incorporates various lexical borrowing in her novel. These include words related to food, living styles, clothing, forms of address and titles, religious terms, Indo-Pak history, traditional wedding events, ethnic identity, languages representing cultural identity, and places symbolizing cultural heritage. Each of these categories reflects the rich cultural and historical context of Pakistan. Second, the study analysed how these lexical variations reflect socio-linguistic practices in Pakistani English. The novel shows the use of code-switching and compounding, two prominent features of Pakistani English that highlight the engaging language use between Urdu and English, blending them to create a distinct linguistic identity. By integrating these cultural-specific words, the writer aims to enhance the authenticity of the story and connect with a broader audience. This shows how language variation reflects the socio-linguistic norms of Pakistani society.